Internet of Things Monitoring System of a Modeled Cleanroom - Rosli, Muhammad Ilias; Ahmad, Mohd Ridzuan (ELEKTRIKA- Journal of Electrical Engineering, 2021)
The development of a cleanroom monitoring system needs more concentrated consideration consistently. There is a challenge to prove that the cleanroom operates following the specifications, in other words, users do not see the software error, they see failures in execution. This paper aims to design a smart monitoring system to monitor important parameters inside the cleanroom, i.e. temperature, humidity, and pressure to produce a good quality of work or experiment inside the cleanroom. The observing framework utilizes Arduino Mega as a microcontroller, ESP 8266 Wi-Fi module, DHT 11 as an integrated temperature and humidity sensor, HX710B as a pressure sensor, and Blynk application as a monitoring system to record and show information including provide fault notification. The project is tested on a modeled cleanroom to monitor important parameters via smartphone anytime and anywhere. From the experimental results, the Cleanroom IoT Monitoring System successfully read all parameters based on the system requirements and displays data of parameters in real-time and stored historical data. This system is also successful to provide failures notification of humidity, temperature, and pressure in real-time if any of the parameters are out of range from the system requirements. Lastly, users can monitor the condition of the cleanroom anytime and anywhere including receiving real-time failures notifications. This concept can avoid or reduce cleanroom working out of the criteria that can cause testing or experiment inside the cleanroom to be inaccurate. By observing and controlling the prerequisite development for IoT monitoring systems, great nature and better quality of performance of operational cleanrooms can be delivered.